Risk and Impact Control of PM2.5 and SO2 Exposure of Power Plant to Communities (A Case Study in the Steam Power Plant Babelan Bekasi) - Belathea Chastine Hutauruk; Dwi Nowo Martono; Ahyahudin Sodri (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: Coal consumption for electrical energy at Steam Power Plant increase often with economic and population growth. Burning coal produces harmful pollutants such as PM2.5 and SO2 affecting public health problems and decline in social and economic conditions. Therefore, implement the strategies are needed to reduce risks and long-term impacts on the environment. The research aimed to analyze the risk and impact of air pollutants exposure and develop control strategies. Methods: This study used the methods of environmental health risk analysis, analysis of the level of understanding and perception, cost of illness analysis, and Strength, Weakness, Opportunities, and Threats analysis, Data obtained by survey, interviews using questionnaire instrument to 293 respondents, five experts to determine risk control strategies and the secondary data from Environmental Agency of Bekasi Regency. Results and Discussion: The result showed that most risk is 13-55 years old, and people who live less than two square kilometres from the power plant. The level of public understanding and perception resulted in moderate criteria. The average cost of illness is 14.51% of the average monthly income of each person. The recommendation strategies are implemented regulations of power plant location, providing guidelines for environmental controlling, air quality control regularly, tightening air quality standards, prioritizing air pollution control budgets, providing green space, implementing clean energy and renewable energy, and building capacity air quality control. Conclusion: The production of electrical energy on Steam Power Plant had an air pollution impact such as health problems, decreased income, and social disruption. Air pollution control includes structural and nonstructural strategies from internal and external Steam Power Plant to provide environmentally friendly energy production for the communities.